Automated facial–vestibulocochlear nerve complex identification based on data‐driven tractography clustering. (6th September 2021) - Zeng, Qingrun; Li, Mengjun; Yuan, Shaonan; He, Jianzhong; Wang, Jingqiang; Chen, Zan; Zhao, Changchen; Chen, Ge; Liang, Jiantao; Li, Mingchu; Feng, Yuanjing
Abstract : Small size and intricate anatomical environment are the main difficulties facing tractography of the facial–vestibulocochlear nerve complex (FVN), and lead to challenges in fiber orientation distribution (FOD) modeling, fiber tracking, region‐of‐interest selection, and fiber filtering. Experts need rich experience in anatomy and tractography, as well as substantial labor costs, to identify the FVN. Thus, we present a pipeline to identify the FVN automatically, in what we believe is the first study of the automated identification of the FVN. First, we created an FVN template. Forty high‐resolution multishell data were used to perform data‐driven fiber clustering based on the multishell multitissue constraint spherical deconvolution FOD model and deterministic tractography. We selected the brainstem and cerebellum (BS‐CB) region as the seed region and removed the fibers that reach other brain regions. We then performed spectral fiber clustering twice. The first clustering was to create a BS‐CB atlas and separate the fibers that pass through the cerebellopontine angle, and the other one was to extract the FVN. Second, we registered the subject‐specific fibers in the space of the FVN template and assigned each fiber to the closest cluster to identify the FVN automatically by spectral embedding. We applied the proposed method to different acquirement sites, including two different healthy datasets and two tumor patient datasets. Experimental results showed that our automatic identification results have ideal colocalization with expert manual identification in terms of spatial overlap and visualization. Importantly, we successfully applied our method to tumor patient data. The FVNs identified by the proposed method were in agreement with intraoperative findings. Abstract : In the current study, an automatic facial–vestibulocochlear nerve (FVN) identification method based on data‐driven tractography clustering is proposed. There was high consistency between automatic and expert manual FVN identification results in terms of spatial overlap and visualization in multiple dMRI acquisition protocol datasets.